(untitled) (Scientific journal of the Fergana State University, 2026)
The use of innovative methods and technologies in primary education is important for developing students’ thinking and forming their independent learning skills. The use of digital technologies in mother tongue education provides broad opportunities for students to increase their vocabulary, compose texts, develop speech communication skills, and form independent thinking and creative approaches.